Climate and culture change in North America AD 900-1600 - Foster, William C., 1928- (Clifton and Shirley Caldwell Texas heritage series ;, 2012)
"Climate change is today's news, but it isn't a new phenomenon. Centuries-long cycles of heating and cooling are well documented for Europe and the North Atlantic. These variations in climate, including the Medieval Warm Period (MWP), AD 900 to 1300, and the early centuries of the Little Ice Age (LIA), AD 1300 to 1600, had a substantial impact on the cultural history of Europe. In this pathfinding volume, William C. Foster marshals extensive evidence that the heating and cooling of the MWP and LIA also occurred in North America and significantly affected the cultural history of Native peoples of the American Southwest, Southern Plains, and Southeast. Correlating climate change data with studies of archaeological sites across the Southwest, Southern Plains, and Southeast, Foster presents the first comprehensive overview of how Native American societies responded to climate variations over seven centuries. He describes how, as in Europe, the MWP ushered in a cultural renaissance, during which population levels surged and Native peoples substantially intensified agriculture, constructed monumental architecture, and produced sophisticated works of art. Foster follows the rise of three dominant cultural centers - Chaco Canyon in New Mexico, Cahokia on the middle Mississippi River, and Casas Grandes in northwestern Chihuahua, Mexico--that reached population levels comparable to those of London and Paris. Then he shows how the LIA reversed the gains of the MWP as population levels and agricultural production sharply declined; Chaco Canyon, Cahokia, and Casas Grandes collapsed; and dozens of smaller villages also collapsed or became fortresses."--PUBLISHER